Implementation Constructivism Approach through Learning Cycle 5E Model to Student Learning Competence Class XI MIA SMA Negeri 12 Padang - Refsya Aulia Fikri; Syamsurizal Syamsurizal; Rahmadhani Fitri (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2018)
Kurikulum 2013 emphasizes science and technology, student centered learning patterns and principles of self-construction to learners. SMA Negeri 12 Padang as the school organizer of Kurikulum 2013 when observation is found non-conformity such as learning conducted is teacher centered, construction of knowledge is less conceptualized in the students. This research is an experimental research with Non-Equivalent Posttest Group Only Design. The study population is the students of class XI MIA SMA Negeri 12 Padang 2017/2018 academic year which spread into four classes. Sampling research using purposive sampling. The results were selected class XI MIA 3 as experimental class and class XI MIA 1 as a control class. The result of t test is known that the knowledge competence of tcount > ttable (2,67 > 1,67), attitude competence tcount > ttable (learning activity: 4,67 > 1,67 and practicum activity: 2,15 > 1,67) , then competence of skill tcount > ttable (2,07 > 1,67). It is known that the hypothesis is accepted. So it can be concluded that the implementation of constructivism approach through Learning Cycle 5E learning model can improve students' learning competence of class XI MIA SMA Negeri 12 Padang.